The Analysis of Banana Slices Machine Frame Using Computational Method - Akmal, Reza Najmi; Julian, James; Wahyuni, Fitri; Purba, Riki Hendra; Toding Bunga, Nely (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2025)
The culinary industry, especially banana chip processing, dramatically supports the economy of micro and small enterprises (MSMEs) in Indonesia. However, the traditional process is time-consuming, especially at the cutting stage. The banana-slicing machine is designed to speed up this process with consistent and efficient cuts. This study analyzes the performance of the banana-slicing machine frame by testing variations in loading (20 N to 200 N) and frame materials, namely Low Alloy Steel, Structural Steel, Stainless Steel, Aluminum Alloy, and Cast Iron, to determine the optimal material. The results showed that Low Alloy Steel is the best material because it has the lowest total deformation, equivalent stress, and strain energy, reflecting high stiffness and load efficiency. With an elastic modulus of 212.5 GPa and an economical price ($1.3–1.5/kg), this material offers the best balance in terms of technical and economics. Structural steel also performed well but was slightly lower than low alloy steel. In contrast, Aluminum Alloy has the highest deformation and strain energy, making it less suitable for this application. Overall, Low Alloy Steel is an ideal choice to improve the efficiency and reliability of the banana-slicing machine.